Distribution of haematological and chemical pathology values among infants in Malawi and Uganda - Kumwenda, Newton I.; Khonje, Tiwonge; Mipando, Linda; Nkanaunena, Kondwani; Katundu, Pauline; Lubega, Irene; Bolton, Steve; Bagenda, Danstan; Mubiru, Michael; Glenn Fowler, Mary; Taha, Taha E.; Ali, Elbireer (Paediatrics and international child health, 2012)
Data on paediatric reference laboratory values are limited for sub-Saharan Africa. Objective: To describe the distribution of haematological and chemical pathology values among healthy infants from Malawi and Uganda. Methods: A cross-sectional study was conducted among healthy infants, 0–6 months old, born to HIVuninfected mothers recruited from two settings in Blantyre, Malawi and Kampala, Uganda. Chemical pathology and haematology parameters were determined using standard methods on blood samples. Descriptive analyses by age-group were performed based on 2004 Division of AIDS Toxicity Table age categories. Mean values and interquartile ranges were compared by site and age-group. Results: A total of 541 infants were included altogether, 294 from Malawi and 247 from Uganda. Overall, the mean laboratory values were comparable between the two sites. Mean alkaline phosphatase levels were lower among infants aged (21 days while aspartate aminotransferase, creatinine, total bilirubin and gamma-glutamyl transferase were higher in those aged 0–7 days than in older infants. Mean haematocrit, haemoglobin and neutrophil counts were higher in the younger age-groups (,35 days) and overall were lower than US norms. Red and white blood cell counts tended to decrease after birth but increased after y2 months of age. Mean basophil counts were higher in Malawi than in Uganda in infants aged 0–1 and 2– 7 days; mean counts for eosinophils (for age groups 8–21 or older) and platelets (for all age groups) were higher in Ugandan than in Malawian infants. Absolute lymphocyte counts increased with infant age. Conclusion: The chemical pathology and haematological values in healthy infants born to HIV-uninfected mothers were comparable in Malawi and Uganda and can serve as useful reference values in these settings.
Keywords: Chemical pathology; Haematology; Infant; Malawi; Reference laboratory value; Uganda